(untitled) (Brazilian Journal of Oceanography, 2004)
The composition and biomass of the microalgal community at the water-column/sediment interface on the continental shelf off Parana State (Brazil) were studied every 2 months during 1999. Samples for cell identification and determination of chlorophyll a were taken from the interface layer and at discrete depths up to 4 m above the sediment. Results showed a community mainly formed by benthic and planktonic diatoms >;30 µm, benthic diatoms ;30 µm, which accounted for most of the pigment biomass, were resuspended from the interface after turbulent periods, and may take advantage of calm periods to stay and grow at the interface. Small benthic diatoms were more susceptible to wind-induced turbulence occurring in higher densities in the water column just above the water-sediment interface. A cyanobacterial bloom (Trichodesmiun) was observed at these bottom layers in the spring-summer periods.